Determinants of value-added tax revenue transfers in municipalities of emerging economies - Brahim Abidar; Slimane Ed-Dafali; Miloudi Kobiyh (Economies, 2025)
This paper aims to test the hypothesis of the existence of significant tax competition between communes, which mainly concerns the share of value-added tax (VAT) proceeds, by exploring the system for allocating intergovernmental transfers in Morocco and analyzing the determinants of VAT transfers to local authorities. It contributes to fiscal federalism by assessing the design of the decentralized system and intergovernmental transfers. It aims to explore and understand the variables determining decentralization in Moroccan Municipalities over the period 2014-2018, based on institutional, budgetary, and political justifications, as well as their influence on local tax efficiency, highlighting the importance of intergovernmental transfers and their impacts on local government autonomy. We find that VAT revenue transfer antecedents include factors such as public expenditure, fiscal potential, tax effort, and political alignment. The results of this study can help better understand the relationship between VAT and economic variables and guide government tax policies in an emerging economy. This paper offers original perspectives on the importance of an informed vision for government decision-makers to develop effective tax policies considering stringent local budget constraints, the need for VAT revenue autonomy across levels of government, and the need for meeting the redistributive goals of the current VAT system.
Keywords: 330; tax policy; value-added tax transfer; redistribution; fiscal transfer; emerging economies; tax revenue; tax reform